Pemanfaatan Limbah Minyak Jelantah Untuk Bahan Dasar Pembuatan Lilin Aromaterapi Sebagai Optimalisasi Kreativitas Ibu-Ibu PKK Di Desa Siwalanpanji - Alamsari Andayani, Endah; Dicky Riza, Moch.; Kotimah, Khusnul; Nurwahyunita, Nina (BERBAKTI : Jurnal Pengabdian Kepada Masyarakat, 2023)
This community service activity aims to optimize the creation of a human resource, including PKK women in Siwalanpanji village, Buduran district, Sidoarjo regency, in the use of waste oil, so that it can produce something of high selling value and economic and social benefits for the surrounding community. The method is lecture, discussion, and direct practice to add innovation and creativity to the village. The socialization results went according to plan and were attended by 40 (forty) representatives of Ms. PKK from each RT in Siwalanpanji Village for 1 (one) month. This socialization activity received a positive response and was greeted with enthusiasm by the PKK women in Siwalanpanji Village. With this activity, used cooking oil waste that accumulates at home can be processed with an innovative touch and creativity can be an additional income for the community.